Arginine: lysine ratio influences on performance, egg quality, haematology, biochemistry, antioxidant status and immunity of dual-purpose breeding hens exposed to cyclic heat stress - Youssef A. Attia; Nicola F. Addeo; Fulvia Bovera; Ahmed A. Abdallah; Rashed A. Alhotan; Abd-El-Hamid E. Abd El-Hamid; Asmaa Sh. Elnaggar; Reada M. Zakey (Italian Journal of Animal Science, 2024)
The aim of this study was to investigate the effects of arginine/lysine ratio (Arg/Lys) on the productive and reproductive performance, egg quality, immune and physiological parameters of hens reared under cyclic heat stress condition (CHS). A total of 140 females, and 20 males of 32 weeks of age, were randomly assigned to 4 treatment groups. The first group (positive control, PC) fed the basal corn-soybean meal diet with an Arg/Lys ratio of 1.25 and was kept at 22–24°C and 45–55% relative humidity. The other 3 treatments fed basal diet in which the Arg/Lys was set at 1.25, 1.37 and 1.50, respectively and were submitted to cyclic heat stress conditions (CHS, 38 °C ± 1, 55–65% RH) for three successive days a week from 10:00 am until 14:00. The results showed a reduction h-day egg production (EP), feed conversion ratio (FCR), shell weight, fertility and hatchability, hemoglobulin (Hgb), hydrogen power (pH) and plasma calcium and phosphorus concentrations for the negative control (NC) group compared to the positive control group. However, changing Arginine (Arg)/lysine (Lys) ratio in the basal diets for the groups under CHS from 1.25 to 1.37 and 1.50 improved EP, egg weight, egg mass and FCR when compared to NC group. Total lipid, total cholesterol, low-density lipoprotein, triglycerides, and malondialdehyde activity for the NC group significantly increased, while increasing the ratio of Arg/Lys to 1.37 and 1.50 improved the mentioned traits as to PC group. Our findings indicated that diets with an Arg/Lys ratio of 1.37 administered to laying hens farmed under cyclic heat stress conditions, are able to improve the laying performance, egg quality, fertility, hatchability, blood hematological and biochemical constituents, antioxidants, and immunity indices in comparison to the other groups, including the PC one. Thus, diets with an Arg/Lys ratio of 1.37 can be used to recover the adverse effect of CHS.